Conceiving Open Systems - Christopher M. Kelty (Washington University Journal of Law & Policy, 2009)
This Article tells the story of the contest over the meaning of "open systems" from 1980 to 1993, a contest to create a simultaneously moral and technical infrastructure within the computer industry.
Keywords: Information technology – Social aspects; Technological innovations; Open source software; Software licensing